2009
DOI: 10.1016/j.ijmultiphaseflow.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent collision of inertial particles: Point-particle based, hybrid simulations and beyond

Abstract: a b s t r a c t Point-particle based direct numerical simulation (PPDNS) has been a productive research tool for studying both single-particle and particle-pair statistics of inertial particles suspended in a turbulent carrier flow. Here we focus on its use in addressing particle-pair statistics relevant to the quantification of turbulent collision rate of inertial particles. PPDNS is particularly useful as the interaction of particles with small-scale (dissipative) turbulent motion of the carrier flow is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 120 publications
0
25
0
Order By: Relevance
“…Particularly, turbulence-mediated collision of heavy particles is vital to efficiency and conversion rates in these processes. 5 Large-eddy simulation ͑LES͒ has emerged as a promising tool for simulating turbulent flows in general and, in recent years, has also been applied to particle-laden turbulence with some successes. 6 The motion of heavy particles is much more complicated than fluid elements, and therefore, LES of turbulent flow laden with heavy particles encounters new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, turbulence-mediated collision of heavy particles is vital to efficiency and conversion rates in these processes. 5 Large-eddy simulation ͑LES͒ has emerged as a promising tool for simulating turbulent flows in general and, in recent years, has also been applied to particle-laden turbulence with some successes. 6 The motion of heavy particles is much more complicated than fluid elements, and therefore, LES of turbulent flow laden with heavy particles encounters new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, transfer the moments m * after the above modification back to the distribution functions as [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where m * means the moment vector after the velocity is constrained. In this procedure, except the velocity, no other macroscopic quantities are changed.…”
Section: The Velocity-constrained Normal Extrapolation Refillingmentioning
confidence: 99%
“…For very small particles, forces including virtual mass force, Basset history force, Saffman force, and Magnus force are negligible as analyzed in our previous work. 23 We have indicated that Brownian motion would lead to considerable collision for fine particles, as described by equation (9) in section ''Collision kernels.'' F D (u 2 v) is the drag force with v being the particle velocity and…”
Section: Particlesmentioning
confidence: 99%
“…Similarly, by including eddy-particle interaction, Zhou et al 11 developed a bidisperse turbulent collision kernel (0.1 \ St \ 5.0). Wang et al 9 recently discussed the collision kernel (0.1 \ St \ 25) using a hybrid direct numerical simulation (HDNS) approach in which the effect of local hydrodynamic interactions of particles is considered. Some reviews on DNS works were summarized by Meyer and Deglon.…”
Section: Inter-particle Collisionmentioning
confidence: 99%